PENYULUHAN POKDARWIS DI DESA WISATA CIKOLELET KABUPATEN BANTEN DALAM LAYANAN PROMOSI DAN KEGIATAN PAKET WISATA - Budilaksono, Sularso; Sovitriana, Rilla; Dewi, Euis Puspita; Nasution, Evi Syafrida; Trikariastoto, ST; Nurina, Nurina; Kencana, Woro Harkandi (Jurnal Abdi Insani, 2024)
The Cikolelet tourist village is a developing tourist village with tourism potential in the form of natural resources, arts and culture and the creative economy of its residents. Its strategic location, not far from Anyer beach, makes this village a destination for students and the general public who are interested in enjoying the tourism being developed. This community service was carried out in the Cikolelet Tourism Village, Banten Regency with the target partner being the Tourism Awareness Group. Pokdarwis. The problems faced by Pokdarwis members are limited human resources, managerial abilities and limitations in carrying out tourism promotions. The aim of this community service is to improve the skills and knowledge of Pokdarwis members in managing tourists. This service method includes counseling, observation and evaluation in practical training. It is hoped that the results of this activity will be able to strengthen the tourism potential in the Cikolelet tourist village and provide direct benefits to the local community. For various fun games, angklung and archery games, adequate infrastructure and facilities are available and the Pokdarwis team has mastered various game methods and techniques. Based on observations and interviews with Pokdarwis members, they have worked and served tourists well, with evidence that there are many homestays, games, food products and good angklung training services. The conclusion of this activity is that participants gain knowledge about homestay management, managerial tourist records, skills in excellent service and bookkeeping of financial reports for payments from tourists.